Economic Security and Sharia Fintech Regulation in Indonesia: A Portrait of Strengthening the Sharia Business Ecosystem - Rohman, Adi Nur; Sugeng; Fitriana, Diana; Aidy, Widya Romasindah (Fiat Justisia: Jurnal Ilmu Hukum, 2023)
The existence of sharia fintech will always be homework for the government. As one of the pillars of economic security, the development of sharia fintech still leaves various problems, especially regarding existing regulations. On the other hand, strengthening the sharia fintech business ecosystem in Indonesia provides a lot of homework to be done. This research is classified as normative legal research that applies a statutory approach regarding primary legal materials in the form of laws and regulations related to sharia fintech and other financial regulations. This study found that the Islamic economic master plan and the Indonesian Islamic financial architecture master plan do not represent the institutions and regulations for Islamic fintech as a sub-sector of Islamic finance that has the potential to develop further. To strengthen the sharia fintech business ecosystem, regulations from relevant authorities are needed that are in line with industrial needs. Strengthening regulations is expected to create a strong and stable economy and accelerate Islamic finance nationally so that Indonesia can become one of the financial centers in South East Asia Region and the world.